(untitled) (Journal of Philosophy, Culture and Political Science, 2025)
The article discusses the issues of the artistic life of the Pavlodar region in the second half of the twentieth century. The object of the study was the artistic culture of the Republic of Kazakhstan and the Pavlodar region in the second half of the twentieth century. Based on the research object, we have identified the subject of scientific work – a general panorama of the artistic life of the Pavlodar region in the second half of the twentieth century. The purpose of the study is to show the general picture of the functioning of various spheres of culture and art in the Pavlodar region during the period under consideration and to identify historical factors that to one extent or another influenced the development of cultural transformations in the Pavlodar region in the second half of the twentieth century. The period we are considering is a time when masters of arts and culture, and creative performing groups were experiencing the heyday of creative transformation. Artistic works of fine and folk applied arts, museums, theatrical art and librarianship, musical art and education, folk and pop songs, a network of palaces and houses of culture, and cinemas all this diversity of cultural development of the Pavlodar region was created by the combined creative work of cultural and art workers. Our history shows that masters of art: writers, painters, sculptors, musicians, theater, and cinema workers are creators who can understand, and truthfully reflect in their works the essence of cultural, political, and social transformations in Kazakhstan and certain regions of our country. Keywords: artistic life, artistic culture, artistic works, fine arts, musical art, theatrical activity, cultural heritage.